URGENSI PENYELESAIAN TUNGGAKAN UANG PENGGANTIYANG DIPUTUS BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 1971 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Lusiana Lamture (2021)
Corruption caused the perpetrators to obtain financial advantages and losses for the country, one of the ways to restore country's lost disadvantages is by providing additional penalty in the form of replacement money. The purpose of this research is to determine the implementation of payment settlement of Replacement Money by the Attorney General of the Republic of Indonesia and the urgency faced in the implementation of the replacement money execution in the corruption crime case based on Law Number 3 of 1971. This research type is normative legal research with legal and conceptual approach. The data analysis in this thesis research is qualitative descriptive. The research results showed that the implementation of payment completion of the arrears in replacement money by the Attorney General of the Republic of Indonesia decided based on Law Number 3 of 1971 is conducted through civil lawsuit and cannot be executed is conducted in installments and still running, until the unresolved arrears and through the deletion attempt of replacement money. The urgency for the Attorney General of the Republic of Indonesia is the large number of settlements of replacement money arrears which overall has not been realized. It is feared that this will have an impact on the administration position of the pending cases.